Making a Difference in the Software Century. - Boehm, Barry (Computer (00189162), 2008)
The article discusses the challenges being faced by software engineers in the 21st century as well as the opportunities to make significant contributions that will make a difference for the better. It is noted that the 21st century will impose large responsibilities to provide excellence in the software-intensive systems that are developed and in the services that they provide. Tensions between people and organizations rapidly adapting to change and those who prefer not to are also anticipated to emerge during the century.